Historical Development of the Education of the Namasudras: The Education of the Namasudras in British Bengal: A Historical Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is a vital role in our life. The term education is derived from a Latin word ‘educatio’ meaning a bringing, a breeding, a rearing. Another Latin word from which the word education comes ‘educere’ implies ‘to draw out”, to lead out”, “to bring forth”. Latin word educatum denotes “to train”, “to teach” Thus, education implies the act of training or teaching the child. The Namasudras constituted the second largest Hindu caste group in the British province of Bengal and the largest in its eastern parts. They lived mainly in the low-lying swamp areas of its six eastern districts, i.e., Bakarganj, Faridpur, Dacca, Mymensingh, Jessore and Khulna In 1881, 71 per cent of the Namasudras of Bengal lived in these six districts.